2017
DOI: 10.1051/smdo/2016012
|View full text |Cite
|
Sign up to set email alerts
|

A MAC based excitation frequency increasing method for structural topology optimization under harmonic excitations

Abstract: -This work is focused on the topology optimization of structures that are subjected to harmonic force excitation with prescribed frequency and amplitude. As an important objective of such a design problem, the natural resonance frequency of the structure is driven far away from the prescribed excitation frequency for the purpose of avoiding resonance and reducing the vibration level. Therefore when the excitation frequency is higher than the natural resonance frequency of the structure, the natural resonance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…In addition, Figure 24 plots the time evolution of the fundamental natural frequency of some intermediate structures obtained at different optimization steps. These results seem to be consistent with other research on time‐invariant problems which found that the optimized structures tend to shift the fundamental natural frequency away from the excitation frequency 13,50 …”
Section: Numerical Examplessupporting
confidence: 91%
“…In addition, Figure 24 plots the time evolution of the fundamental natural frequency of some intermediate structures obtained at different optimization steps. These results seem to be consistent with other research on time‐invariant problems which found that the optimized structures tend to shift the fundamental natural frequency away from the excitation frequency 13,50 …”
Section: Numerical Examplessupporting
confidence: 91%
“…In another study, the dynamic behavior of the fixtured workpiece subjected to time-and space-varying machining loads is simulated using a forced vibration model [12]. Topology optimization of structures with damping that is exposed to harmonic force excitation with prearranged frequency higher than its natural resonance frequency is done in another study [13].…”
Section: Introductionmentioning
confidence: 99%